Multi-wavelength studies of the X-ray binary MAXI J1727 − 203: constraining system parameters. Issue 4 (2nd June 2022) - Wang, Sili; Kawai, Nobuyuki; Shidatsu, Megumi; Murata, Katsuhiro; Hosokawa, Ryohei; Hanayama, Hidekazu; Horiuchi, Takashi; Morihana, Kumiko
ABSTRACT: We report on the evolution of X-ray spectral and timing properties of the X-ray binary MAXI J1727 − 203 based on NICER/XTI and MAXI/GSC observations. Over the course of the outburst, a transition from the intermediate state to the high/soft state, and then back to the low/hard state was observed. During the high/soft state, the innermost radius estimated from the multi-colour disc model remained constant at $\sim 145.0\ (\frac{D}{10\ kpc}) \ {(\frac{\cos i}{\cos 0^{° }})}^{-1/2}$ km, where D is the source distance and i is the inclination. Assuming that the binary system contain a Schwarzschild black hole and has an inclination angle of 0°–84°, and considering the typical Eddington ratio at the transition back to the low/hard state, the black hole mass was estimated to be M ≥ 11.5 M⊙ for a distance of D ≥ 5.9 kpc. We also attempted to constrain the black hole mass and distance with a different method by combining the results from optical and near-infrared photometric observations. We modelled the near-infrared to X-ray spectral energy distributions obtained in the outburst period with an irradiated disk model, and estimated the lower limit of the black hole mass for a given distance, assuming both accretion disk and companion star fill their Roche lobe. The lower limit was, however, found to be much higher than the constraint obtained from the X-ray data. We discuss several possible causes of this inconsistency. It is difficult to fully resolve the conflict by a single cause and hence a combination of causes is required.